(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2020)
The gatekeepers for institutions of fine arts, classical music and theatre in Australia are traditionally white, upper middle-class people. Nakkiah Lui’s existence and success as an Indigenous playwright is a radical disturbance in this bubble of society as, by nature, stories and storytellers that challenge cultural hegemony will always be political, and Blak artists entering theatre demonstrate a fusion and adaptation of Indigenous oral traditions into Australia’s highbrow society. Aboriginal playwrights and performances have a complex history in terms of audience reception as they often deal with difficult and confronting topics that ‘regular’ theatre audiences may not engage with (Grehan 2010). Not only do they have the burden of representing ‘all’ Aboriginal people, but the stories they share are often those whose voices were historically silenced, erased or dismissed (Morris 1992).